ANALISIS CEDERA OLAHRAGA DAN PENANGANAN DI PUSAT LAYANAN FISIOTERAPI OLAHRAGA DAN KEBUGARAN FAKULTAS ILMU KEOLAHRAGAAN UNIVERSITAS NEGERI PADANG: ANALYSIS OF SPORTS INJURIES AND THEIR MANAGEMENT AT THE SPORTS AND FITNESS PHYSICAL THERAPY SERVICE CENTER, FACULTY OF SPORTS SCIENCES, PADANG STATE UNIVERSITY - Tiara Aulia; Syafrianto, Donal; Bahtra, Ridho; Liza (Jurnal IKEOR, 2026)
Abstract: This study is motivated by the absence of structured data regarding visit patterns, user characteristics, types of treatment, and service trends at the Sports Physiotherapy and Fitness Service Center (Labor Sport Medicine) of the Faculty of Sports Science, Universitas Negeri Padang. This study uses a quantitative descriptive method with a retrospective approach. Data were collected through documentation of the laboratory’s visit records from January 2021 to December 2025. The total population as well as the study sample consisted of 548 service visits meeting the inclusion criteria. The results show that the total visits over five years amounted to 548, with a significant upward trend, especially in 2024 (185 visits; 33.8%) coinciding with the 2024 National Sports Week (PON). Users were dominated by athletes (40.3%), male (71.90%), and aged 18–25 years (43.24%). The most common complaint location was the lower extremity (37.04%), especially the knee (24.45%). The most frequently provided service was massage therapy (45.4%), followed by sports physiotherapy (42.3%). The most common treatment modality was TENS/Interferential (21.13%). The primary cause of visits was fitness/recovery (41.2%) and intrinsic non-contact factors (19.9%). Repeat visits accounted for 29.56% of total visits.